2023
DOI: 10.1002/ana.26710
|View full text |Cite|
|
Sign up to set email alerts
|

Regional Glymphatic Abnormality in Behavioral Variant Frontotemporal Dementia

Abstract: ObjectivesGlymphatic function has not yet been explored in behavioral variant frontotemporal dementia (bvFTD). The spatial correlation between regional glymphatic function and bvFTD remains unknown.MethodA total of 74 patients with bvFTD and 67 age‐ and sex‐matched healthy controls (HCs) were selected from discovery dataset and replication dataset. All participants underwent neuropsychological assessment. Glymphatic measures including choroid plexus (CP) volume, diffusion tensor imaging along the perivascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…1 A–C. As previously noted in a prior study [ 28 ], it was suggested that ROIs in the anterior and posterior regions may exhibit distinct regional glymphatic clearance effects. Therefore, we conducted further adjustments by shifting our manually corrected middle ROIs one and two voxels forward and one and two voxels backward along the y -axis.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…1 A–C. As previously noted in a prior study [ 28 ], it was suggested that ROIs in the anterior and posterior regions may exhibit distinct regional glymphatic clearance effects. Therefore, we conducted further adjustments by shifting our manually corrected middle ROIs one and two voxels forward and one and two voxels backward along the y -axis.…”
Section: Methodssupporting
confidence: 57%
“…This method has also been applied to quantify in vivo glymphatic activity in various neurological disorders, including idiopathic normal pressure hydrocephalus (iNPH) [ 25 ], Parkinson’s disease [ 26 ], and multiple sclerosis [ 27 ] (MS), consistently revealing that reduced DTI-ALPS values are associated with disease severity. Choroid plexus volume, suggested as a driving force behind glymphatic function, has demonstrated associations with disease severity in conditions like frontotemporal dementia (FTD) [ 28 ] and AD [ 29 ] and has been used to predict conversion to Parkinson’s disease dementia [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the efficacy of the ALPS index in detecting human glymphatic function has not yet been substantially and rigorously validated by pathophysiological studies. While the ALPS index has been confirmed by glymphatic MRI 11 and has been extensively studied in various diseases, 14,15,51 it should be interpreted with caution. Second, the ALPS index was used to assess the global glymphatic activity and cannot reflect regional glymphatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, several methods have been developed that may reveal regional glymphatic activity. [54][55][56] Therefore, the relationship between the DTI-ALPS index and glycemic clearance should be interpreted with caution. The sequential effect among glymphatic dysfunction, tau deposition, and clinical symptoms needs to be verified in longitudinal studies.…”
Section: Limitationsmentioning
confidence: 99%